The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.37275/arkus.v9i1.281
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Emotional Intelligence on the Development of Critical Thinking: A Study of Department of Accounting Students, Universitas Negeri Malang, Indonesia

Abstract: The accounting learning process requires students to have critical thinking skills. Critical thinking is called the process of making judgments based on analysis, interpretation, evaluation, inference, explanation, and reflection. Many factors influence critical thinking, one of which is emotional intelligence. Another factor that can influence critical thinking is conflict management. This study aimed to determine the role of emotional intelligence and the ability to manage conflict from students that affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Further comprehensive research is necessary to clarify the effects of AI capabilities. The factors affecting critical thinking are diverse [28], including general selfefficacy [29], learning motivation [30], cognition [31], emotional intelligence [32], and the environment [33]. Previous studies have shown that general self-efficacy and learning approaches play a crucial role in developing critical thinking skills [34].…”
Section: Scenarios Of Ai Education Ai-related Technologymentioning
confidence: 99%
“…Further comprehensive research is necessary to clarify the effects of AI capabilities. The factors affecting critical thinking are diverse [28], including general selfefficacy [29], learning motivation [30], cognition [31], emotional intelligence [32], and the environment [33]. Previous studies have shown that general self-efficacy and learning approaches play a crucial role in developing critical thinking skills [34].…”
Section: Scenarios Of Ai Education Ai-related Technologymentioning
confidence: 99%